(untitled) (Plant Tissue Culture and Biotechnology, 2025)
Banana (Musa spp.) is an economically important fruit crop cultivated globally, including Bangladesh. Efficient in vitro propagation is crucial for large-scale production of disease-free planting materials. This study aimed to optimize the concentration of 6-benzylaminopurine (BAP) for mass micropropagation of two banana cultivars, the red banana (Agnishwar) and the G9 (Grand Naine) Cavendish cultivar. Shoot tip explants were cultured on MS medium supplemented with 1.0 mg/l 1-naphthaleneacetic acid (NAA) and varying concentrations of BAP (1.0-6.0 mg/l). The effect of BAP on shoot multiplication, shoot elongation, leaf number and root induction were assessed at 60 days after culture (DAC). Results showed that shoot multiplication was significantly influenced by BAP concentration, while shoot elongation and leaf number exhibited significant results for genotype × BAP interactions. The highest shoot length (27.88 cm) was recorded in G9 at 6.0 mg/l BAP, whereas Agnishwar attained a maximum shoot length of 13.04 cm at 3.0 mg/l BAP. Leaf number was significantly affected at 1% level, with G9 producing more leaves than Agnishwar. Root induction efficiency remained unaffected by BAP concentrations, though genotype-specific responses were observed. Ex vitro acclimatization of micropropagated plantlets demonstrated high survival rates (83.33% for G9 and 81.25% for Agnishwar), confirming the effectiveness of the optimized protocol. The BAP concentration plays a critical role in shoot multiplication, shoot elongation and leaf development, with genotypic variations influencing response to in vitro conditions. The optimized protocol can facilitate large-scale propagation of high-quality planting materials for sustainable banana production in Bangladesh. Plant Tissue Cult. & Biotech. 35(1): 51-65, 2025 (June)